Preliminary studies of the tardigrada communities from a polymetallic nodule area of the deep South China Sea - Wang, Xiaogu; Bai, Lifen; Wang, Chunsheng; Lu, Bo; Li, Yujie; Lin, Qinyi; Huang, Xinyu; Fontoura, Paulo (Frontiers in Marine Science, 2023)
Knowledge about marine tardigrades from the South China Sea is very scarce, with only four species from shallow waters recorded to date. The present study investigated the structure and diversity of tardigrade communities from the deep sea (1517-1725 m) at 8 stations in a polymetallic nodule area of the northern South China Sea. A total of 151 arthrotardigrades were collected belonging to 11 genera (Angursa, Batillipes, Coronarctus, Euclavarctus, Exoclavarctus, Halechiniscus, Moebjergarctus, Raiarctus, Rhomboarctus, Tanarctus and Tholoarctus), representing 17 species. Two Angursa species (Angursa sp. 4 and Angursa sp. 3) were the most abundant (25.2% and 14.6%, respectively), followed by Moebjergarctus sp. (13.9%). Specimens were mostly (90.7%) distributed in the upper layer of the sandy-mud sediment (0-1 cm). The SIMPROF test showed that the composition of tardigrade communities at all stations was not significantly different. At different stations, the number of species, Shannon-Wiener diversity index and Pielou’s evenness index ranged from 4 to 10, 1.94 to 2.87, and 0.75 to 1.00, respectively. The average taxonomic distinctness (Δ+) ranged from 72.50 to 90.00, and the variation in taxonomic distinctness (Λ+) ranged from 316.67 to 1181.25. This study provides some basic information about the biodiversity of the marine tardigrade community in the South China Sea.